Managed care and community health centers. - Shi L; Frick KD; Lefkowitz B; Tillman J (Journal of Ambulatory Care Management, 2000)
This study has two objectives: (1) to examine the relationship between the involvement of community health centers (CHCs) in managed care and various center characteristics, including patient, provider, services, and financial characteristics, that are critically linked with the fulfillment of their mission and (2) to identify factors significantly associated with CHCs' involvement in managed care. Regarding the first objective, the study indicates that CHCs involved in managed care have more diversified sources of revenue and depend less on grant funding than other CHCs, and they serve a significantly smaller proportion of uninsured and homeless patients. Involvement in managed care is also associated with greater financial vulnerability, reflected in higher costs and net revenue deficits. Regarding the second objective, the study finds that CHCs have become involved in managed care largely in response to external market pressures, such as the prospect of reduced federal grant funding. Other significant factors include center size, location, and the percentage of users who are Medicaid patients. Copyright © 1999 by Aspen Publishers, Inc.